Reconstruction of Family Time–Based Visitation Services for Female Prisoners: An Analysis of Relational Justice in Correctional Institutions in Lampung Province - Sri Rahayu; Agung Adiansyah; Bayu Suseno (Universitas Islam Negeri Raden Intan Lampung, 2025)
The restriction of family visitation in correctional institutions has a significant impact on marital harmony among female prisoners and impedes their process of social reintegration. This study aims to analyze the implications of visitation service policies on the family relationships of female inmates and to formulate a model for reconstructing visitation services based on a just and equitable family time framework. This research employs a qualitative approach with an empirical juridical and multidisciplinary design, conducted in three female correctional institutions in Lampung Province. Data were collected through in-depth interviews with 42 female prisoners, analysis was carried out using theories of justice, legal psychology, and mubādalah (reciprocity-based Islamic legal reasoning). The findings indicate that 31% of female prisoners experienced marital disharmony that correlates with the limited duration of family visitation. Visitation policies that are predominantly formalistic and brief have not adequately fulfilled the emotional, psychological, and relational needs of female inmates, particularly those who hold dual roles as wives and mothers. This study recommends the reconstruction of visitation services through a structured family time program and contributes to the development of family law in Indonesia.